Structural characterisation of carbon nanotubes in the presence of a Ni catalyst - Edwards, H.K.; Fay, Mike W.; Bououdina, M.; Gregory, D.H.; Walker, G.S.; Brown, Paul D. (Institute of Physics Publishing, 2004)
Multi-wall carbon nanotubes (MWNTs) grown by chemical vapour deposition (CVD) of an ethene / hydrogen gas mixture on alumina supported and unsupported nickel catalysts for 10, 20 and 120 minutes at 600oC and 700oC are compared. Nano-scale nickel particles were identified at the tube ends and also within the main body of the tubes. The particles exhibited comet like structures suggesting the metal to be highly mobile if not molten during processing. HREM observations demonstrate the carbon planes to be parallel to the nickel particle surfaces, while eventually becoming drawn out to define the carbon tube walls. The tubes are generally found to emanate from larger encapsulated nickel particles. A growth mechanism involving the propulsion of mobile nickel through the precipitation of the carbon is discussed.